Biodiversity and Health in the Face of Climate Change 2019
DOI: 10.1007/978-3-030-02318-8_7
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Foundations of Biodiversity and Mental Well-being Relationships

Abstract: This chapter briefly describes six frameworks that offer perspective on the relationships between biodiverse natural environments and mental well-being. The aim of this chapter is to provide an overview of these frameworks to enable theoretical grounding of future biodiversity and mental well-being studies. The frameworks are largely from the field of environmental psychology and represent the majority of theories used in biodiversity and health research (The Preference Matrix; fractal geometry; the Biophilia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Two theories of restorative environments are proposed to explain the health benefits of green exercise [34]. Environments that facilitate the restoration of the individual's depleted cognitive capacities for information processing are called restorative [35]. First, the psycho-evolutionary stress recovery theory posits that exposure to nature promotes stress reduction by providing positive distractions from daily stressors and developing feelings of calmness or interest, which may in turn foster positive affect and decrease stress [27].…”
Section: Ecological Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two theories of restorative environments are proposed to explain the health benefits of green exercise [34]. Environments that facilitate the restoration of the individual's depleted cognitive capacities for information processing are called restorative [35]. First, the psycho-evolutionary stress recovery theory posits that exposure to nature promotes stress reduction by providing positive distractions from daily stressors and developing feelings of calmness or interest, which may in turn foster positive affect and decrease stress [27].…”
Section: Ecological Dynamicsmentioning
confidence: 99%
“…According to this framework, the foundation of environmental preferences is the desire to obtain information from the environment. The exploration of the immediate environment depends on the complexity of the stimuli (i.e., the number of different visual elements in a scene), the coherence (i.e., provides a sense of order), the legibility (i.e., easy to understand and to remember), and mystery (i.e., the promise of additional information) [35]. In this framework, we can find the study by van den Berg et al [38], who analyzed whether perceived complexity of natural and urban scenes would explain differences in viewing times and ratings of mental restoration.…”
Section: Ecological Dynamicsmentioning
confidence: 99%
“…Biodiversity is not addressed in the theoretical writings of the ART (Marselle, 2019). However, natural environments providing specific components of biodiversity may be beneficial for attention restoration as they are likely to contain stimuli that facilitate the experience of all four restorative qualities (Korpela, Pasanen and Ratcliffe, 2018;Marselle, 2019).…”
Section: Attention Restoration Theorymentioning
confidence: 99%
“…Biodiversity is not addressed in the theoretical writings of the ART (Marselle, 2019). However, natural environments providing specific components of biodiversity may be beneficial for attention restoration as they are likely to contain stimuli that facilitate the experience of all four restorative qualities (Korpela, Pasanen and Ratcliffe, 2018;Marselle, 2019). One study found restoration from directed attention fatigue was greatest for people who looked at images of urban greenspaces with high vegetation density compared to those who looked at urban greenspaces with medium-or low-density vegetation (Chiang, Li and Jane, 2017).…”
Section: Attention Restoration Theorymentioning
confidence: 99%
“…Biodiversity, e.g. richness of species, is hypothesised as something that could contribute to the fascination quality of a restorative environment (Ulrich 1983; see Marselle 2018). It could also contribute to a conceptual sense of 'being away', an additional dimension of this restorative environment feature (Kaplan, S. 1995).…”
Section: Setting Componentmentioning
confidence: 99%